2020
DOI: 10.3390/healthcare8040508
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Innovative Work Behavior, Job Anxiety, Workplace Ostracism, and Workplace Incivility: Empirical Evidence from Small and Medium Sized Enterprises (SMEs)

Abstract: The aim of this study is to explore the relationship between workplace ostracism (WO), workplace incivility (WI), and innovative work behavior (IWB), using job anxiety as a mediating variable. Building on the conservation of resource (COR) theory, this study proposes a theoretical framework. In this framework, workplace ostracism and workplace incivility are theorized to strengthen innovative work behavior, directly and indirectly, through job anxiety. Data were collected from the workers of small and medium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 78 publications
4
63
0
2
Order By: Relevance
“…This growth has partly stemmed from the rapid development of small and medium-size enterprises (SMEs) within China. Currently, small and medium-size enterprises employ 80% of the workforce in China [ 1 , 2 ]. One reason why SMEs have flourished this way is that small and medium-size enterprises have fewer regulations imposed on them as compared to large enterprises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth has partly stemmed from the rapid development of small and medium-size enterprises (SMEs) within China. Currently, small and medium-size enterprises employ 80% of the workforce in China [ 1 , 2 ]. One reason why SMEs have flourished this way is that small and medium-size enterprises have fewer regulations imposed on them as compared to large enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…However, employees belonging to SMEs have to suffer from a lower pay and a high level of toxic workplace environment, such as workplace harassment, workplace bullying, and workplace ostracism [ 3 ]. Such an environment is a significant detriment toward employee motivation and engagement, and prior studies have shown that a toxic workplace environment in small and medium-size enterprises plays a negative role toward employee engagement [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corporations can effectively develop robust, positive relationships among workers, supervisors, and managers by viewing employee welfare as an important, socially responsible, and necessary practice [ 52 , 53 ]. Providing a comfortable working environment can increase employees’ job satisfaction and encourage them to share new ideas and knowledge [ 11 , 13 , 54 ]. Survey-based research supports the positive influence of employee on innovation.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…First, innovation is a complex process that largely relies on human capital [ 1 , 6 ]. Employee care may play crucial role in facilitating innovation because employees may actively find new ideas and create knowledge if they have high levels of job satisfaction [ 11 , 13 , 54 ]. According to the knowledge-based view, firms’ ability of innovation is derived from the control and use of valuable knowledge [ 51 , 67 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation